2016
DOI: 10.1021/acs.bioconjchem.6b00473
|View full text |Cite
|
Sign up to set email alerts
|

Brightly Luminescent and Kinetically Inert Lanthanide Bioprobes Based on Linear and Preorganized Chelators

Abstract: The synthesis, photophysical properties and kinetic stability of a series of water-soluble, highly emissive Tb(III) and Eu(III) complexes featuring triethylenetetraamine hexaacetic acid (TTHA) and cyclohexyl triethylenetetraamine hexaacetic acid (cyTTHA) chelator scaffolds and carbostyril sensitizers are reported. The unique and modular design of the chelators gives rise to striking quantum yields of emission in aqueous solutions (up to 54%) as well as the characteristic lanthanides’ photophysical properties (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…For cell-impermeable lanthanides, techniques, such as micro-injection, 27,44 reversible plasma membrane permeabilization, 45 and osmotic lysis of pinocytic vesicles, 29,45 have been used. Co-incubation with compounds that increase cell permeability such as DMSO, 30,46,47 saponin, 34 or TMPyP 48 has also been described.…”
Section: Endocytosismentioning
confidence: 99%
“…For cell-impermeable lanthanides, techniques, such as micro-injection, 27,44 reversible plasma membrane permeabilization, 45 and osmotic lysis of pinocytic vesicles, 29,45 have been used. Co-incubation with compounds that increase cell permeability such as DMSO, 30,46,47 saponin, 34 or TMPyP 48 has also been described.…”
Section: Endocytosismentioning
confidence: 99%
“…There are also a few examples of core N-substitutions (alkylations). 34 The effects of exocyclic N-alkylations on Ln sensitization have not been studied in detail, presumably because changes were expected to be small. We hypothesised that the removal of the N-H bond may have a measurable effect on the Ln emission quantum yield, at least for the more sensitive Eu complexes.…”
Section: Introductionmentioning
confidence: 99%
“…20 We also demonstrated that Cy-TTHA analogues were substantially more kinetically inert than their linear counterparts, as evidenced by an EDTA challenge assay. In order to prepare brightly emissive complexes, we needed an efficient synthetic approach that permitted selective mono-substitution of chromophoric sensitizer moieties at designated pendant positions.…”
mentioning
confidence: 66%
“…1–3 Due to their ability to provide high denticities via a hard base binding core (carboxylate ions and tertiary amines), their corresponding lanthanide complexes have been heavily studied. 420 While linear polyaminopolycarboxylates form thermodynamically stable complexes, their relative kinetic instability with respect to many metals such as Gd(III) can limit their utility in biological or clinical environments. 2125 In contrast, the widely used macrocyclic polyaminocarboxylates DOTA and TETA (Fig.…”
mentioning
confidence: 99%